2015
DOI: 10.1037/tra0000023
|View full text |Cite
|
Sign up to set email alerts
|

Abuse in childhood and psychopathic traits in a sample of violent offenders.

Abstract: A significant body of research underlines the link between the exposure to abuse in childhood and subsequent criminal behaviors. Research on the role played by childhood interpersonal trauma in the development of psychopathy, however, is still scant. The aim of this study was to explore the relationship between childhood experiences of abuse and psychopathic traits in a group of violent offenders from Italy. Seventy-eight inmates who were convicted of violent crimes participated in this study. Participants wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 54 publications
3
33
0
2
Order By: Relevance
“…A more recent hypothesis (Schraft, Kosson, & McBride, 2013) states that child maltreatment is a risk factor that could increase the probability of a more serious and maladaptive expression of the psychopathic dimension, as it affects the normal development of some basic skills such as affective modulation, empathy, mentalization, and interpersonal and self-regulation (Schimmenti, Di Carlo, Passanisi, & Caretti, 2015). Other authors (Waxman, Fenton, Skodol, Grant, & Hasin, 2014) identified significant correlations between the increase of some Psychopathy Checklist-Revised (PCL-R) components, such as "lifestyle" and "antisocial behavior" (F2 factor) (Hare, 2003) and physical abuse by male figures during childhood.…”
Section: Introductionmentioning
confidence: 99%
“…A more recent hypothesis (Schraft, Kosson, & McBride, 2013) states that child maltreatment is a risk factor that could increase the probability of a more serious and maladaptive expression of the psychopathic dimension, as it affects the normal development of some basic skills such as affective modulation, empathy, mentalization, and interpersonal and self-regulation (Schimmenti, Di Carlo, Passanisi, & Caretti, 2015). Other authors (Waxman, Fenton, Skodol, Grant, & Hasin, 2014) identified significant correlations between the increase of some Psychopathy Checklist-Revised (PCL-R) components, such as "lifestyle" and "antisocial behavior" (F2 factor) (Hare, 2003) and physical abuse by male figures during childhood.…”
Section: Introductionmentioning
confidence: 99%
“…Feelings of shame are often associated with infertility. The internalization of unworthy or abusing parents (18) may also play a role in causing such emotion together with dysfunctional attitudes (i.e. insecure attachment and problematic internet use) (19,20) and disadaptive disorders (i.e.…”
Section: © C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 99%
“…Proportions were compared with chi-square test ( 2). A logistic regression analysis was performed to control for covariates that differed in our two groups despite randomization.…”
Section: © C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 99%